2009
DOI: 10.1080/00268970903213305
|View full text |Cite
|
Sign up to set email alerts
|

Ab initiopair potential energy curve for the argon atom pair and thermophysical properties of the dilute argon gas. I. Argon–argon interatomic potential and rovibrational spectra

Abstract: initio pair potential energy curve for the argon atom pair and thermophysical properties of the dilute argon gas. I. Argon-argon interatomic potential and rovibrational spectra. Molecular Physics, Taylor & Francis, 2009, 107 (20) An argon-argon interatomic potential energy curve was derived from quantum-mechanical ab initio calculations using basis sets of up to d-aug-cc-pV(6+d)Z quality supplemented with bond functions and ab initio methods up to CCSDT(Q). In addition, corrections for relativistic effects wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
92
1
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(104 citation statements)
references
References 34 publications
4
92
1
7
Order By: Relevance
“…Here we show that a seventh-order ab initio virial EOS for argon [20][21][22] gives rise to (high-temperature) JT inversion data in excellent agreement with the reference data set 5 up to the maximum inversion pressure. We also argue that the obtained JT inversion curves provide some insight into the range of applicability and high-density behavior of the truncated virial EOS.…”
Section: -20mentioning
confidence: 48%
See 1 more Smart Citation
“…Here we show that a seventh-order ab initio virial EOS for argon [20][21][22] gives rise to (high-temperature) JT inversion data in excellent agreement with the reference data set 5 up to the maximum inversion pressure. We also argue that the obtained JT inversion curves provide some insight into the range of applicability and high-density behavior of the truncated virial EOS.…”
Section: -20mentioning
confidence: 48%
“…Jäger et al have reported smooth temperaturedependencies of B 2 to B 7 in terms of fits (of Laurent polynomials in √ T ) to discrete B n data computed from ab initio two-body 21,22 and non-additive three-body potentials. 22 We use these fits to compute the JT inversion curve by solving…”
Section: -20mentioning
confidence: 99%
“…Although more accurate ab initio pair potentials for argon have become available recently, 5,6 and other many-body contributions to inter-atom interaction can be calculated, 8 we use the same interaction as Nasrabad et al because, being able to predict accurately the phase diagram of argon, 16 it is computationally more efficient. Specifically, the ab initio pair interaction potential used in the present work is described by a function…”
Section: Interactionmentioning
confidence: 99%
“…Several experimental results obtained for argon at large pressures are better explained if a larger steepness, compared to Lennard-Jones, of argon-argon interaction potential at small inter-atomic separation distances is taken into account. 2,3 Accurate argonargon interatomic potentials have been calculated by direct ab initio quantum chemical calculations [4][5][6] or obtained by inversion of experimental data. 7 Moreover, many-body dispersion, exchange and induced polarization contributions to inter-atomic interactions are not small and noticeably influence thermodynamic properties of argon.…”
Section: Introductionmentioning
confidence: 99%
“…There is also significant emphasis on developing ab initio interatomic potential by using quantum chemical calculations and using it to predict bulk phase properties. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] The potential energy surface for a large number of configurations is generated to fit to the functional form of the force field. This approach is, however, limited to moderately sized molecules with limited conformational degrees of freedom as the computational cost increases significantly with the complexity of the molecule.…”
Section: Introductionmentioning
confidence: 99%